PENERAPAN PROMOSI PENJUALAN UNTUK MENINGKATKAN OMSET PENJUALAN PADA UD HAMIDA KUE BANJARMASIN - Rika Sylvia; Mailiana Mailiana; Reffani Fajar (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, The purpose of this study was to determine the application of sales promotions conducted at UD Hamida Kue to increase sales turnover. This type of research is descriptive qualitative, with sampling using incidental sampling, while the data analysis technique used is descriptive statistics. The conclusion of this study is based on the results of respondents' responses regarding sales promotions implemented by UD Hamida Kue, that for the variable of business promotion through the provision of a sample of 25 respondents (50%) stated agree, cash return of 23 respondents (46%) agreed, and special prices of 25 respondents (50%) agreed. For trade promotion variables through direct discounts, 25 respondents (50%) agreed and free goods in the form of packaging, 20 respondents (40%) agreed. While the variable of business promotion through trade shows as many as 20 respondents (40%) agreed.